2010
DOI: 10.1016/j.jesp.2009.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dissonance induced by writing a counterattitudinal essay facilitates performance on simple tasks but not on complex tasks that involve working memory

Abstract: To cite this version:Marie-Amélie Martinie, Thierry Olive, Laurent Milland. Cognitive dissonance induced by writing a counterattitudinal essay facilitates performance on simple tasks but not on complex tasks that involve working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…However, the situation is different for the monitoring and the resolution of inconsistency. If, however, the amount of relevant information is large or the required inferences are rather complex, the cognitive resources that are required for the identification and resolution of inconsistency will be more substantial (e.g., Martinie, Olive, & Milland, 2010; see also Wilson, Lindsey, & Schooler, 2000). However, when people engage in a conscious and intentional assessment of particular pieces of information, limits in working memory capacity will constrain (a) how much information they can hold simultaneously in memory and (b) the complexity of syllogistic inferences they can perform to assess the consistency of this information.…”
Section: Efficiencymentioning
confidence: 99%
“…However, the situation is different for the monitoring and the resolution of inconsistency. If, however, the amount of relevant information is large or the required inferences are rather complex, the cognitive resources that are required for the identification and resolution of inconsistency will be more substantial (e.g., Martinie, Olive, & Milland, 2010; see also Wilson, Lindsey, & Schooler, 2000). However, when people engage in a conscious and intentional assessment of particular pieces of information, limits in working memory capacity will constrain (a) how much information they can hold simultaneously in memory and (b) the complexity of syllogistic inferences they can perform to assess the consistency of this information.…”
Section: Efficiencymentioning
confidence: 99%
“…More importantly, the increase in arousal related to dissonance may explain why dissonance facilitates performance in simple tasks. For instance, Martinie et al () collected the reaction times of participants who were writing counterattitudinal essays in dissonance and no‐dissonance conditions. The participants in the dissonance condition had shorter reaction times than those in the no‐dissonance condition.…”
Section: Measuring the Arousal Related To Dissonancementioning
confidence: 99%
“…The participants in the dissonance condition had shorter reaction times than those in the no‐dissonance condition. Martinie et al () interpreted this finding within the framework of the energetic models of cognitive resources (see Sanders, , for an example), which postulate that the level of arousal affects the total amount of available cognitive resources. For instance, the shorter reaction times observed in dissonance condition indicated more available cognitive resources, which resulted from an increase in participants' level of arousal.…”
Section: Measuring the Arousal Related To Dissonancementioning
confidence: 99%
“…Martinie, Olive, and Milland (2010) found that requiring individuals to endorse positions counter to their own attitudes impaired performance on complex cognitive tasks requiring working memory. Martinie et al suggested the reason for this finding might be that taking part in counterattitudinal behaviors creates intmsive thoughts that siphon off cognitive resources.…”
Section: The Influence Of Value Conflict On Therapy Outcomesmentioning
confidence: 99%